2019
DOI: 10.1080/21691401.2019.1645151
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Long noncoding RNA HAGLROS promotes the process of mantle cell lymphoma by regulating miR-100/ATG5 axis and involving in PI3K/AKT/mTOR signal

Abstract: This research planned to grab the expression and impact of lncRNA HAGLROS in the biology and progression of mantle cell lymphoma. HAGLROS level in mantle cell lymphoma cell lines was detected, followed by investigation of the influences of HAGLROS silencing on Mino cell biological performances. Afterwards, the express patterns of HAGLROS vs. miR-100, as well as miR-100 vs. ATG5, were investigated. Furthermore, whether HAGLROS could regulate the signals of PI3K/AKT/mTOR was analyzed. HAGLROS level was high in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Recently, with the rapid development of biology, more and more RNA biomolecules are used as clinical markers of cancer [24]. For example, microRNA-195, microRNA-223, microRNA-221, microRNA-421, and microRNA-203 in serum are differently expressed in OS tissues, indicating that they can be used as a new biomarker for screening OS to predict poor prognosis and monitor the progress of cancer [17,[25][26][27][28]. In the present study, we found that circCCDC66 was overexpressed in tumor cells compared to normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the rapid development of biology, more and more RNA biomolecules are used as clinical markers of cancer [24]. For example, microRNA-195, microRNA-223, microRNA-221, microRNA-421, and microRNA-203 in serum are differently expressed in OS tissues, indicating that they can be used as a new biomarker for screening OS to predict poor prognosis and monitor the progress of cancer [17,[25][26][27][28]. In the present study, we found that circCCDC66 was overexpressed in tumor cells compared to normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in mice transplanted with HO-1-MSCs or treated with anisomycin, the autophagy in GCs can be obviously activated, shown as increased levels of LC3-II, beclin1, and Atg5 but decreased p62. It is known that increased levels of autophagosomes can enhance its own formation and/or block the lysosomal processing [45]. In this study, decreased number of autophagosomes and receded intensity of fluorescence by MDC were observed in mice transplanted with shHO-1-MSCs or treated with SP600125, also with the observation of nucleolus shrinked and chromatin condensation.…”
Section: Discussionmentioning
confidence: 51%
“…PI3K/AKT/mTOR pathway is commonly accepted as a vital pathway in controlling cancer progression, and lncRNA as ceRNA has been validated to mediate tumorigenesis and development through PI3K/AKT/ mTOR pathway [24,25]. LPAR3 has been manifested to be tightly related to PI3K/AKT pathway in ovarian cancer [16].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the significance of PI3K/AKT/mTOR pathway as well as its close relation to lncRNA-mediated ceRNA mechanism [24,25], we wondered whether ZEB1-AS1 involved in this pathway. Through western blot assay, the protein levels of PI3K, AKT and mTOR were hardly changed, whereas their phosphorylation levels were remarkably weakened in ZEB1-AS1 silenced cells, and partially rescued by LPAR3 overexpression.…”
Section: Zeb1-as1 Exerts Oncogenic Effect On Tc Progression By Activamentioning
confidence: 99%